Colorectal Carcinoma Presenting as Ovarian Metastasis: A Case Report - A, Haikal; C, Haikal; S, Thiesfeldt; N, Bou Zgheib; D, Griswold (Archives of Clinical and Medical Case Reports, 2020)
There is a common occurrence of colorectal adenocarcinoma metastasis to the ovary and in rare circumstances, these cases may present clinically as primary ovarian cancer and histologically as primary endometrioid carcinoma of the ovary. Approximately 3.6% to 7.4% of patients with colon cancer have ovarian metastasis at the time of initial presentation, of which, 45% are mistaken for primary ovarian tumors. The author reports the case of a 60-year-old female presenting with fatigue and pelvic pain secondary to a pelvic mass. Computed tomography (CT) revealed a lobulated, heterogeneous pelvic mass measuring 11.1 × 10.5 × 9.8 cm, and ultrasound (US) showed complex 13.8 × 8.2 × 12.3 cm mass posterior to the uterus. Upon examination of the specimen following debulking procedure, endometrioid carcinoma of the ovaries was initially considered. However, immunohistochemical stains were performed and showed malignant cells positive for cytokeratin (CK) 20, caudal type homeobox (CDX) 2, and specific AT-rich sequence binding (SATB) protein 2, consistent with metastatic colorectal carcinoma. This report highlights the diagnostic challenges arising with differentiation between primary endometrioid ovarian carcinoma and metastatic colorectal adenocarcinoma to the ovary and the potential clinical consequences of misdiagnosis.